Practices of self medication among university students of Multan, Pakistan - Ishfaq, Kamran; Rizwan, Muhammad; Ahmad Warraich, Imtiaz; Mohamad Diah, Nurazzura; Fayyaz, Bareera (2019)
The objective of present study is to determine the practices of self-medication among university students of Multan, Pakistan. A cross sectional study was carried out at Bahauddin Zakariya University Multan and Nishtar Medical University Multan, Pakistan. The data was collected from 300 medical and 300 non medical students with the help of convenient sampling. Close ended questionnaire were developed for the data collection. Of the 600 respondents 300 were medical while 300 were non medical students. There were 169(28.2%) male and 431(71.8%) were females. Majority of the respondents were Muslims 591(98.5%) while 9(1.5%) were non Muslims. The most frequent signs and symptoms that led students to involve in self medication were headache 279(46.5%), flu 102(17.0%), fever 101(16.8%), pain elsewhere 39(6.5%), anti allergies 28(4.7%), diarrhea 25(4.2%), 26(4.3%) for other reasons. Majority of the medical and non medical university students used commonly drugs, pain killer 411(68.5%), antibiotics 67(11.2%), Vitamins 51(8.5%), anti allergies 30(5.0%), sleeping pills 17(2.8%) herbal/ tonics 7(1.2%), and any other 5(.8%). Majority of the respondents reported that they practices self medication is due to the easy availability of common drugs 370(61.7%) while 104(17.3%) discussed that due to habit they used self medication, 85(14.2%) thought that there is no side effect. In our study there was no significant difference in practicing self medication amongst the medical and non medical students. A holistic approach should be implemented to prevent this important problem especially education and awareness towards the implication of self medication.